Study of Coronary Collaterals in Patients with Stable Angina (University Heart Journal, 2011)
Background: Coronary collateral circulation is an alternative source of blood supply to the myocardium in coronary atherosclerotic disease. They provide adequate flow to the major epicardial branches of the coronary artery. Indicator of cardiac ischemia like stable angina pectoris may determine the presence of coronary collateral circulation.Methods and results: In this prospective observational cross sectional study, 150 patients with stable angina pectoris with or without MI (myocardial infarction) and or coronary intervention were enrolled. Presence of coronary collaterals in coronary angiogram was defined as Rentrop grade > 1. Patients were divided into two groups. Group A patients having Rentrop grade 0 and Group B patients are with collateral circulation, having Rentrop grade 1-3. Patients are compared in these groups. Total (63%) patients with stable angina were in Group B with coronary collateral circulation and only (37%) patients with stable angina pectoris were in Group A without collaterals.Conclusions: The incidence of development of coronary collaterals was significantly higher in patients with stable angina pectoris. DOI: 10.3329/uhj.v6i2.7245University Heart Journal Vol. 6, No. 2, July 2010 pp.61-64